How to Be an Unsuccessful Ancient Philosophy Scholar in Uneasy Times: The Case of S. Lisiecki (1872-1960) - Mróz, Tomasz (Peitho. Examina Antiqua, 2023)
The paper provides a brief outline of the biography and works of Stanisław Lisiecki (1872–1960), a little-known Polish classics scholar, who is remembered only, if at all, as a translator of Plato’s Republic. In his early fifties, having given up his career as a Catholic priest, he started working in the field of classics and managed to publish several minor works on Plato in Polish and Latin. His decision to abandon the clergy was not welcomed by many members of the Polish academia and most of his translations of Plato and Aristotle remained unpublished. His renderings of Plato could not compete with the highly accessible translations made by W. Witwicki, which were becoming increasingly popular at that time. Furthermore, Lisiecki’s translations of Aristotle, despite the pioneering nature of his undertaking, met with strong criticism at various university seminars.